Kedudukan Anak Perempuan Sebagai Ahli Waris Dalam Hukum Adat Batak Toba - Lumbantoruan, Simson Hasgelter; Rosando, Abraham Ferry (CV. Era Digital Nusantara, 2025)
The position of daughters as heirs in Batak Toba customary law has experienced dynamics along with the development of the times and the influence of gender equality values. This study normatively analyzes the changes that occur in the position of daughters as heirs, as well as their implications for the application of Batak Toba customary law in modern society. This study uses a normative legal research method by analyzing various relevant legal sources and materials. The results of this study indicate that the Batak Toba tribe adheres to patrilineal family traits, so only sons are heirs to their parents' assets. If their parents' assets are obtained from their grandfather, then the son as the successor is entitled to the grandfather's inheritance. The results of this study are expected to contribute to a more comprehensive understanding of the position of daughters in Batak Toba customary inheritance law, as well as provide recommendations to the government for the improvement of related laws and regulations.